Discourse, Fiscal Policy, and Economic Justice: A Critical Analysis of the Narrative of Credit Restructuring for Inclusive Growth in Indonesia - Isnaeni Isnaeni; Sry Wahyuni (Journal of Scientific Insights, 2026)
This study examines the relationship between discourse, financial policy, and economic justice in Indonesia through a critical analysis of the narrative surrounding credit restructuring as presented in the president’s speeches. Using a Critical Discourse Analysis (CDA) approach, this study aims to reveal how language is used to construct, legitimize, and critique economic policies related to credit access for various social groups, particularly large business owners and marginalized groups such as fishermen. The research data consists of speech acts in the president’s public addresses, analyzed based on rhetorical strategies, lexical choices, and implicit meanings that reflect power relations and ideological positions. The findings indicate that this discourse simultaneously critiques the privileges of the economic elite while constructing a narrative of financial policy that is more inclusive for underrepresented groups. Furthermore, linguistic strategies such as irony, repetition, and contrast play a crucial role in reinforcing messages of economic justice and policy reform. This study contributes to interdisciplinary research by integrating linguistic analysis with economic policy discourse, and offers insights into the role of language in shaping public perceptions of financial inclusion and equitable growth. This study is also relevant to the Sustainable Development Goals (SDGs), particularly SDG 10.3 on reducing inequalities of outcome and ensuring equal opportunities in access to economic resources, as well as SDG 16.6 concerning the development of effective, accountable, and transparent institutions. Through the analysis of financial policy discourse, this study highlights how political language constructs narratives of economic justice, financial inclusion, and institutional responsibility in addressing unequal access to credit in Indonesia.